2009
DOI: 10.1002/prca.200900112
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous expressions of hepcidin isoforms in hepatoma‐derived cells detected using simultaneous LC‐MS/MS

Abstract: Hepcidin, a key regulator of iron homeostasis, is known to have three isoforms: hepcidin-20, -22, and -25. Hepcidin-25 is thought to be the major isoform and the only one known to be involved in iron metabolism; the physiological roles of other isoforms are poorly understood. Because of its involvement in the pathophysiology of hereditary hemochromatosis and the anemia of chronic disease, the regulatory mechanisms of hepcidin expression have been extensively investigated, but most studies have been performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…To overcome this intrinsic problem for high cysteine containing peptides, some researchers utilize the immonium ion for SRM transitions with high cleavage energy, which results in reduced sensitivity [27]. In this study, we found that the N-terminal residue of hepcidin, namely, H 2 N-Asp-Thr-His-Phe-Pro-Ile, which is free of cysteines, demonstrated a linear dissociation efficiency by collision-induced dissociation and SRM transitions.…”
Section: Resultsmentioning
confidence: 74%
“…To overcome this intrinsic problem for high cysteine containing peptides, some researchers utilize the immonium ion for SRM transitions with high cleavage energy, which results in reduced sensitivity [27]. In this study, we found that the N-terminal residue of hepcidin, namely, H 2 N-Asp-Thr-His-Phe-Pro-Ile, which is free of cysteines, demonstrated a linear dissociation efficiency by collision-induced dissociation and SRM transitions.…”
Section: Resultsmentioning
confidence: 74%
“…This LC-tandem MS method was useful because it is able to measure all three hepcidin isoforms in serum simultaneously [22]. We also investigated how the three hepcidin isoforms are processed, as well as the role hepatocytes may play in hepcidin processing.…”
Section: Introductionmentioning
confidence: 99%
“…25 While physiological roles of the other two isoforms (hepcidin-20 and -22) have been detected in human urine and hepatomaderived cells, they are poorly understood. 25,26 As hepcidin mRNA expression in peripheral leukocytes was found to be associated with neither serum ferritin nor iron in the present study, and its regulatory mechanism was different from that in hepatocytes, it is reasonable to speculate that hepcidin expressed in peripheral leukocytes in response to inflammation may exert immune modulating functions beyond iron metabolism. Further studies testing the protein levels of hepcidin via validated methodology, such as mass spectrometric assay, 26 are warranted to verify whether the hepcidin proteins expressed in peripheral immune cells are the same as those from hepatoma-derived cells.…”
mentioning
confidence: 59%